Risk of Fungal Infection to Dental Patients - Jaqueline Lopes Damasceno; Rafael Aparecido dos Santos; Amir Horiquini Barbosa; Luciana Assirati Casemiro; Regina Helena Pires; Carlos Henrique Gomes Martins (The Scientific World Journal)
Fungi can cause various diseases, and some pathogenic fungi have been detected in the water of dental equipment. This environment offers suitable conditions for fungal biofilms to emerge, which can facilitate mycological contamination. This study verified whether the water employed in the dental units of two dental clinics at the University of Franca was contaminated with fungi. This study also evaluated the ability of the detected fungi to form biofilms. The high-revving engine contained the largest average amount of fungi, 14.93 ± 18.18 CFU/mL. The main fungal species verified in this equipment belonged to the genera Aspergillus spp., Fusarium spp., Candida spp., and Rhodotorula spp. Among the isolated filamentous fungi, only one fungus of the genus Fusarium spp. did not form biofilms. As for yeasts, all the Candida spp. isolates grew as biofilm, but none of the Rhodotorula spp. isolates demonstrated this ability. Given that professionals and patients are often exposed to water and aerosols generated by the dental procedure, the several fungal species detected herein represent a potential risk especially to immunocompromised patients undergoing dental treatment. Therefore, frequent microbiological monitoring of the water employed in dental equipment is crucial to reduce the presence of contaminants.